Phosphorylation in the Catalytic Cleft Stabilizes and Attracts Domains of a Phosphohexomutase - Xu, Jia (Biophys J, 2015)
Phosphorylation can modulate the activities of enzymes. The phosphoryl donor in the catalytic cleft of α-D-phosphohexomutases is transiently dephosphorylated while the reaction intermediate completes a 180° reorientation within the cleft. The phosphorylated form of 52 kDa bacterial phosphomannomutase/phosphoglucomutase is less accessible to dye or protease, more stable to chemical denaturation, and widely stabilized against NMR-detected hydrogen exchange across the core of domain 3 to juxtaposed domain 4 (each by ≥1.3 kcal/mol) and parts of domains 1 and 2. However, phosphorylation accelerates hydrogen exchange in specific regions of domains 1 and 2, including a metal-binding residue in the active site. Electrostatic field lines reveal attraction across the catalytic cleft between phosphorylated Ser-108 and domain 4, but repulsion when Ser-108 is dephosphorylated. Molecular dynamics (MD) simulated the dephosphorylated form to be expanded due to enhanced rotational freedom of domain 4. The contacts and fluctuations of the MD trajectories enabled correct simulation of more than 80% of sites that undergo either protection or deprotection from hydrogen exchange due to phosphorylation. Electrostatic attraction in the phosphorylated enzyme accounts for 1) domain 4 drawing closer to domains 1 and 3; 2) decreased accessibility; and 3) increased stability within these domains. The electrostriction due to phosphorylation may help capture substrate, whereas the opening of the cleft upon transient dephosphorylation allows rotation of the intermediate. The long-range effects of phosphorylation on hydrogen exchange parallel reports on protein kinases, suggesting a conceptual link among these multidomain, phosphoryl transfer enzymes.